Palaeoenvironmental conditions for the preservation of organic matter during the late Hauterivian in the Neuquén Basin (Western Argentina). (October 2020) - Omarini, Julieta; Lescano, Marina; Odino-Barreto, Andrea Lorena; Campetella, Débora; Tunik, Maísa; Garbán, Grony; Brea, Fabián; Erra, Georgina; Aguirre-Urreta, Beatriz; Martinez, Mathieu
Abstract: The Agua de la Mula Member of the Agrio Formation, comprises marine deposits accumulated in a mixed carbonate-siliciclastic outer ramp during the late Hauterivian. An innovative multi-proxy study that includes sedimentological, geochemical and paleobiological data from the El Portón section were combined in order to constrain the environmental context. Two major sedimentary cycles have been recognised (TST-HST) reflecting the position of both distal and proximal sediments within the depositional system. The distal outer ramp deposits (FA1) are predominantly characterised by carbonate-bearing mudstones, with TOC content up to 4.43 wt% TOC (average 1.62 wt%) and Type II marine-derived amorphous organic matter. The high TOC could be reflecting enhanced bioproductivity during periods of decreased salinity as mirrored by peaks of Micrantholithus, and reduced dilution by siliciclastic material in a distal setting. Conversely, the proximal outer ramp succession (FA2) shows a higher siliciclastic pattern, along with the terrestrial organic matter signal (Type II-III kerogen) and TOC content around 1 wt% (average 1.05 wt%). In this interval primary production is associated with more stable conditions and stratified water, as reflected in peaks of Nannoconus. These conditions allowed a greater diversity and high abundances of calcareous nannofossil assemblages. Graphical abstract: Image 1 Highlights: A sequence stratigraphy analysis of a mixed carbonate-siliciclastic ramp was performed. High TOC is associated with mudstones facies within the TST and low HST intervals. Kerogen is Type II and II-III and ranges from immature to early mature. TOC and nannofossils abundance changes allows to predict palaeoenvironmental variations.